Spin structure and spin Hall magnetoresistance of epitaxial thin films of the insulating non-collinear antiferromagnet SmFeO3 - Hajiri, Tetsuya; Baldrati, L.; Lebrun, Romain; Filianina, M.; Ross, Andrew; Tanahashi, N.; Kuroda, M.; Gan, W. L.; Mentes, T. O.; Genuzio, Francesca; Locatelli, Andrea; Asano, Hidefumi; et al. (Journal of Physics: Condensed Matter, 2019)
We report a combined study of imaging the antiferromagnetic (AFM) spin structure and measuring the spin Hall magnetoresistance (SMR) in epitaxial thin films of the insulating non-collinear antiferromagnet SmFeO3. X-ray magnetic linear dichroism photoemission electron microscopy measurements reveal that the AFM spins of the SmFeO3(1 1 0) align in the plane of the film. Angularly dependent magnetoresistance measurements show that SmFeO3/Ta bilayers exhibit a positive SMR, in contrast to the negative SMR expected in previously studied collinear AFMs. The SMR amplitude increases linearly with increasing external magnetic field at higher magnetic fields, suggesting that field-induced canting of the AFM spins plays an important role. In contrast, around the coercive field, no detectable SMR signal is observed, indicating that the SMR of the AFM and canting magnetization components cancel out. Below 50 K, the SMR amplitude increases sizably by a factor of two as compared to room temperature, which likely correlates with the long-range ordering of the Sm ions. Our results show that the SMR is a sensitive technique for non-equilibrium spin systems of non-collinear AFMs.
CRIS-Team Scopus Importer:2023-03-27
Keywords: antiferromagnet; orthoferrite; PEEM; spin Hall magnetoresistance; x-ray magnetic linear dichroism